A Study on the Optimized Design for Responding to Climate Change Through Demonstration of Building Energy Cooling Load Element Technology - Tae Gyun Yun; Seung-Joon Lee; Seok-Pyo Kang; Beung Yong Park; Hoang Minh Duc; Nguyen Duc Luong (Energies)
This study proposes a building energy element technology system that addresses cooling loads, in response to rising average temperatures due to global warming caused by climate change. The study analyzes performance variations and energy-saving potential based on design parameters of individual element technologies, utilizing both simulation and field demonstration to derive an integrated Cooling Load Package System (CPS). The methodology comprises three key steps: (1) identifying and selecting element technologies suitable for optimal building design under subtropical climate conditions, (2) employing the building energy simulation software EnergyPlus v9.6.0 to evaluate the energy performance of each technology and establish prioritization based on energy-saving potential, and (3) conducting local climate validation through the construction of an outdoor demonstration site in northern Vietnam to assess the real-world energy-saving effectiveness of the proposed CPS.